2021
DOI: 10.1111/ijac.13940
|View full text |Cite
|
Sign up to set email alerts
|

Development of spark plasma sintered conductive SiC–TiB2 composites for electrical discharge machining applications

Abstract: Highly dense electrically conductive silicon carbide (SiC)–(0, 10, 20, and 30 vol%) titanium boride (TiB2) composites with 10 vol% of Y2O3–AlN additives were fabricated at a relatively low temperature of 1800°C by spark plasma sintering in nitrogen atmosphere. Phase analysis of sintered composites reveals suppressed β→α phase transformation due to low sintering temperature, nitride additives, and nitrogen sintering atmosphere. With increase in TiB2 content, hardness increased from 20.6 to 23.7 GPa and fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…When the electric field intensity exceeds 1 × 10 6 V/m, the discharge can be generated in the air [30]. Figure 9 presents that the discharge energy increases with the growing interelectrode distance.…”
Section: (B) Discharge Energy Experimental Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the electric field intensity exceeds 1 × 10 6 V/m, the discharge can be generated in the air [30]. Figure 9 presents that the discharge energy increases with the growing interelectrode distance.…”
Section: (B) Discharge Energy Experimental Analysesmentioning
confidence: 99%
“…From Figure 9, it can also be found that the effective discharge distance of the interelectrode decreases with the increasing discharge concentration. When the electric field intensity exceeds 1 × 10 6 V/m, the discharge can be generated in the air [30]. Figure 9 presents that the discharge energy increases with the growing interelectrode distance.…”
Section: The Machining Experimentsmentioning
confidence: 99%